The Regulation of Agriculture in Developing East Asia - Divanbeigi, Raian; Kayumova, Marina (World Bank, Washington, DC, 2017)
Developing countries across East Asia have made impressive progress in economic development. Despite the effect of the 1997-1998 financial crisis, poverty rates in the region have been consistently declining. Agriculture played a key role by driving growth in the early stages of industrialization. It also contributed to reducing rural poverty by including smallholders into modern food markets and creating jobs in agriculture and agroindustry. As incomes rise and countries urbanize, the composition of domestic food expenditure is shifting from basic and unprocessed staple foods to meat, horticulture and processed foods. In order to take full advantage of these emerging trade opportunities policy makers across East Asian countries must support agribusinesses with effective regulations. Benchmarking regulatory frameworks in East Asian economies through the EBA indicators suggests few general trends. First, these countries tend to perform better on efficiency than on legal components. Second, most countries over perform the global average on fertilizer regulations but fail to do so when regulating seed systems. Third, access to markets and finance regulations are two areas where regulation in the region is particularly weak.